The Influence Of Light And Temperature On The Germination Of Two Ugandan Medicinal Trees - Stangeland, Torunn; Tabuti, John R. S.; Lye, Ka°re A. (African Journal of Ecology, 2008)
For reasons of the problems of establishment of some Ugandan trees in certain environments, we investigated the influence of temperature and light on germination and seedling growth of two locally threatened medicinal trees, Hallea rubrostipulata and Sarcocephalus latifolius, to facilitate their establishment. Field and controlled laboratory experiments were carried out to investigate the species germination requirements and seedling growth. Both species needed light to germinate. Hallea rubrostipulata had a temperature optimum of 25°C with 79% germination, while for S. latifolius, the total germination after 28 days was close to 60% at temperatures from 20 to 35°C. Seedlings of S. latifolius survived well at 35°C, while those of H. rubrostipulata died at this high temperature. Conversely, seedling of S. latifolius died at the low temperature of 15°C. However, in field experiment S. latifolius failed to germinate in the available degraded environments, probably because of predation and because the soil is not able to retain water long enough to support seedling growth. We, therefore, conclude that in this part of Uganda, nursery assistance is needed to establish healthy populations of Sarcocephalus and many other endangered trees.
Keywords: conservation, germination, Hallea rubrostipulata, medicinal plants, Sarcocephalus latifolius, seedling growth